Mechanism-based treatment strategies for IBD: Cytokines, cell adhesion molecules, JAK inhibitors, gut flora, and more - Schreiner, Philipp; Neurath, Markus; Ng, Siew C.; El-Omar, Emad M.; Sharara, Ala I.; Kobayashi, Taku; Hisamatsu, Tadakazu; Hibi, Toshifumi; Rogler, Gerhard (Inflammatory Intestinal Diseases, 2019)
Background: Although TNF inhibitors revolutionized the therapy of inflammatory bowel disease (IBD), we have been reaching a point where other therapies with different mechanisms of action are necessary. A rising number of elderly IBD patients with contraindications to established therapies and a growing group of patients losing response to anti-TNF therapy compel us to find safer, better-tolerated, and, ideally, personalized treatment options. However, in order to choose the right drug to fit a patient, it is indispensable to understand the pathomechanism involved in IBD. Summary: The aim of this review is to explain the inflammatory signaling pathways in IBD and how to inhibit them with current and future therapeutic approaches. Next to biologic agents targeting inflammatory cytokines (anti-TNF agents, anti-IL-12/-23 agents, and specific inhibitors of IL-23), biologics blocking leukocyte trafficking to the gut (anti-integrin antibodies) are available nowadays. More recently, small molecules inhibiting the JAK-STAT pathway (JAK inhibitors) or preventing lymphocyte trafficking (sphingosine-1-phosphate modulators) have been approved or are under investigation. Furthermore, modifying the microbiota has potential therapeutic effects on IBD, and autologous hematopoietic or mesenchymal stem cell transplantation may be considered for a highly selected group of IBD patients. Key Message: Physicians should understand the different mechanisms of action of the potential therapies for IBD to select the right drug for the right patient.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Biologics; Crohn's disease; Inflammatory bowel disease; Small molecules; Ulcerative colitis